2016
DOI: 10.1177/0022034516629116
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic RCT on the Efficacy of Proximal Caries Infiltration

Abstract: Proximal caries infiltration has been shown to be efficacious in hampering caries lesion progression when performed by dentists working in a university setting. The aim of this randomized split-mouth, placebo-controlled clinical trial was to assess the efficacy of resin infiltration of proximal caries lesions being performed by several dentists in private practices, in combination with individualized oral hygiene plus noninvasive measures compared with these alone. In this study, 87 children and young adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 17 publications
2
51
0
12
Order By: Relevance
“…The results demonstrate that after 3.5 years, proximal sealing on the sound mesial surfaces of the first permanent molars were efficacious in preventing the development of dental caries. These are findings that are in line with the findings of recent reports showing that sealing and infiltration methods are efficacious in reducing the progression of non-cavitated proximal lesions [Dorri et al, 2015;Schwendicke et al, 2015;Meyer-Lueckel et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
“…The results demonstrate that after 3.5 years, proximal sealing on the sound mesial surfaces of the first permanent molars were efficacious in preventing the development of dental caries. These are findings that are in line with the findings of recent reports showing that sealing and infiltration methods are efficacious in reducing the progression of non-cavitated proximal lesions [Dorri et al, 2015;Schwendicke et al, 2015;Meyer-Lueckel et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
“…In this case, a false 8 8 positive result may be perceived as caries progression. These reasons may explain the lower rate of caries progression in this and other studies [11,16,17,21]. The results of this study in terms of caries progression were evaluated using DSR, in which to increase the noticeable changes in radiographs, the structured noise is reduced.…”
Section: Discussionmentioning
confidence: 82%
“…Likewise, resin infiltration was shown to be effective in the prevention of the progression of interface caries in both primary and permanent teeth in other studies [11,16,17,21,22,24,25]. Meyer-Lueckel et al [11] reported on the 3-year impact of resin infiltration to prevent the progression of proximal non-cavitated caries lesions compared to placebo treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations